Odpowiedzi

2009-12-10T16:32:41+01:00
Przekształć iloczyny na sumy :
a)3b(2b+3)= 6b^2 + 9b
b)k³(4k-1)= 4k^4 - k^3
Zapisz w najprostszej postaci :
x(-2x-1)-(2x³-6x²-4x):(-2)= -2x^2 -x -2x^3 +6x^2 +4x= -2x^3 + 4x^2 +3x

(-2x+2y-12): 0,5= -4x + 4y -24
1 5 1
Najlepsza Odpowiedź!
2009-12-10T16:34:51+01:00
3b(2b+3)=6b²+9b

k³(4k-1)=4k₄-k³

x(-2x-1)-(2x³-6x²-4x):(-2)=(x-2x-1-2x³-6x²-4x) :(-2)=(-5x-1-2x³-6x²) :(-2)=2,5x+½-x³+3x²

(-2x+2y-12): 0,5=-4x+4y-24



licze na naj
1 5 1
2009-12-10T16:35:49+01:00
Przekształć iloczyny na sumy :
a)3b(2b+3)=6b do potęgi 2 + 9b
b)k³(4k-1)=4k do potęgi 4 - k do potęgi 3
1 5 1